Karakteristik Tafsir Sufistik Indonesia - Muhammad Yahya; Muhammad Rijal Maulana; Eni Zulaiha; Edi Komarudin (UIN Sunan Gunung Djati Bandung, 2022)
This paper aims to discuss Sufistic interpretations in Indonesia and try to explore the meaning of Sufism and Tarekat, then connect them to the understanding of the Qur'an. The method of this paper is qualitative with a literature study approach. In addition to discussing the influence of Sufism and tarekat, this article also discusses the mufasir figures from Indonesia. In summary, Sufism entered Indonesia around the 17th century based on the historical text pioneered by Hamzah Fansuri. Holistically, the distinctive form of Sufsitik interpretation is divided into two, namely, Isyari and Nazhari interpretations. However, among Indonesian scholars of interpretation who are also experts in the science of Sufism, none of them wrote their commentaries using Sufistic styles in the form of Isyari and Nadzari. This is because they separate the science of Sufism from the science of interpretation. Therefore, they still rely on the textual meaning and the rules of interpretation generally.